2019
DOI: 10.1007/s13659-019-00218-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Alpha-Mangostin to Dengue Virus Replication and Cytokines Expression in Human Peripheral Blood Mononuclear Cells

Abstract: Massive pro-inflammatory cytokines production has been correlated with the pathogenesis of severe dengue disease. The active compound of mangosteen fruit pericarps, α-mangostin, has been commonly used as traditional medicine and dietary supplement. We examined the effect of α-mangostin against dengue virus (DENV) infection in human peripheral blood mononuclear cells (PBMC) by the measurement of virus titer and TNF-α and IFN-γ cytokines concentration post infection. Increasing concentration of α-mangostin inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Several studies reported that it possesses a wide range of biological activities including anti-inflammatory, anti-allergic, antiviral, antibacterial, antifungal, anti-parasitic, antioxidant, and anti-cancer properties [ 27 , 28 ]. Earlier studies have also shown that α-Mangostin can inhibit DENV in peripheral blood mononuclear cells and hepatic cell lines and down-regulate the expression of pro-inflammatory cytokines [ 29 , 30 ]. These studies have shown the effect of α-Mangostin post-infection.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that it possesses a wide range of biological activities including anti-inflammatory, anti-allergic, antiviral, antibacterial, antifungal, anti-parasitic, antioxidant, and anti-cancer properties [ 27 , 28 ]. Earlier studies have also shown that α-Mangostin can inhibit DENV in peripheral blood mononuclear cells and hepatic cell lines and down-regulate the expression of pro-inflammatory cytokines [ 29 , 30 ]. These studies have shown the effect of α-Mangostin post-infection.…”
Section: Discussionmentioning
confidence: 99%
“…The ethanolic extract of mangosteen fruit is considered as a potent inhibitor of HIV‐1 protease activity and the antiviral property of this fruit is due to the presence of purified molecules like α‐mangostin and γ‐mangostin (Chen et al., 1996 ). The administration of α‐mangostin (obtained from the pericarps of mangosteen) to dengue patients during the acute phase of illness may decrease infection severity by activating the host’s immune response through mechanism of interfering DENV NS5 protein activity which is essential for DENV replication and reducing transcriptional responses of cytokines (Sugiyanto et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of α‐mangostin against the DENV infection and post‐infection in PBMCs, TNF‐α and IFN‐γ cytokines revealed that increasing concentration of α‐mangostin inhibits the viral replication by more than 50% with the IC 50 of 5.47 and 5.77 μM for 24 and 48 hr of post‐treatments, respectively (Sugiyanto et al., 2019 ). The α‐mangostin inhibits DENV production in cultured hepatocellular carcinoma HepG2 and Huh‐7 cells, and cytokine/chemokine expression in HepG2 cells (Tarasuk et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antioxidant and neuroprotective effects of α-mangostin on 6-hydroxydopamine-induced toxicity in SH-SY5Y cells as an in vitro model for Parkinson's disease have been demonstrated. [22] Moreover, α-mangostin has been found to inhibit the production of both dengue virus and cytokines/chemokines, [23] act as antiviral and anti-inflammatory agent in the treatment of dengue fever, [24] have a biological role via the TAK1-NF-κB pathway against inflammation, [25] induce the necrotic death of BT474 breast cancer cells through autophagy and inflammation, [26] and exhibit inhibitory effects on cholangiocarcinoma cells and allografts. [27] The α-mangostin showed apoptotic effect on human breast cancer cells via inhibiting activity of fatty acid synthase (FAS), [28] abrogates anoikis resistance in human hepatocellular carcinoma cells [19] and migration and invasion of A549 lung cancer cells.…”
Section: Introductionmentioning
confidence: 99%